2003
DOI: 10.1111/j.1432-2277.2003.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent changes in cyclosporine exposure: implications for achieving target concentrations

Abstract: This study analyzed early changes in trough blood cyclosporine concentrations and cyclosporine exposures after kidney transplantation. Seventy-two patients who received cyclosporine-based immunosuppressive therapy were intensively monitored (CO) during the first 6 months after transplantation. Full pharmacokinetic studies were performed at day 4, and months 2, 3, and 6 after transplantation. Mean steady-state, dose-adjusted trough cyclosporine blood concentrations increased from 1.1 f 0.60 (day 7) to 2.0 i 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…dosing, is constant but it can change increasingly with time postoperatively. This tendency suggests the need for higher postoperative doses that may be tapered later on (8). This variation in F would affect the primary compartmental disposition parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dosing, is constant but it can change increasingly with time postoperatively. This tendency suggests the need for higher postoperative doses that may be tapered later on (8). This variation in F would affect the primary compartmental disposition parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This last parameter varies widely between 21% and 73%, being lower immediately after renal allograft reception, and it is possibly a critical factor in explaining the observed unpredictability in the early kinetics, i.e. in the monitored blood concentration ( C b ) and the dose (3, 8).…”
Section: Introductionmentioning
confidence: 99%
“…These studies are important to identify better immunosuppressive regimens for our patients, taking into account the unique demography of our transplant population, which is quite different from that reported in the US or Europe. We have been participants in of the majority of international clinical trials and have also performed local research with immunosuppressive drugs including new combi- nations of cyclosporine (19,20); reduced doses of OKT3 (21), tacrolimus (22), sirolimus (23), everolimus (24), mycophenolate mofetil (25), and mycophenolate sodium (26); and FTY720 (27,28). To implement our research program, we have developed techniques to measure blood levels of sirolimus and mycophenolic acid (16,17).…”
Section: Researchmentioning
confidence: 99%
“…In addition, this requirement to higher initial doses of drug may be partly due to the low initial CsA absorption and the low relative bioavailability early after transplantation. Felipe et al reported a significant increasing time-dependent in steady state of CsA exposure occurred within the first month of kidney transplantation (14). It has been reported that a high intra-individual variability of C0 concentrations is associated with a greater incidence of acute and chronic rejection episodes, reduced 5-year graft survival and increased serum creatinine (15).…”
Section: Discussionmentioning
confidence: 99%